(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
From the last few decades, the use of concrete-filled steel tubular (CFST) columns has been very popular particularly Due to rapid on-going horizontal development and restricted vertical development of buildings has resulted in congestion of cities and shrinkage of agricultural land, particularly in high seismic zones. For vertical development, there is a need for the construction of buildings as high as possible. The restriction to the vertical development is due to the reason that high rise structures are more vulnerable to lateral loads acting on the building resulting from the seismic events. With a background in view, the current work studies the seismic responses of a multi-storey complex building with concrete-filled steel tube columns (CFST). In the present study, three buildings with plan dimensions 35m x 30m of G+12 stories, with earthquake zone-V and soil type medium were modelled with varying columns types. The design and analysis were carried out using equivalent static method and response spectrum method as per IS-1893 2016. The total height of the building was taken as 42m with the height of each floor as 3.5m. The conclusion was made after studying parameters like Base Shear, Max. story displacement, Max. storey drift, Total Dead load of the structure, Max. time period, and Storey Shear. All the building models meet the allowable limit for safe design. It was concluded that the building with CFST columns has better resistance at high seismic zones and the cross-sectional dimensions required by building with CFST columns to pass the design check are lesser than the other types of columns.